Synthesis and Characterization of CaO-Zeolite Catalyst by Sonochemical Engineering Method - Widyarini Widyarini; Muhammad Djoni Bustan; Sri Haryati (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2022)
Calcium Oxide (CaO) loaded on zeolite was categorized as a heterogeneous catalyst. The utilization of CaO catalyst could be implemented in catalytic pyrolysis enhance gaseous production. In this paper, CaSO4.2H2O is an active site embedded in natural zeolite, and the activity of the CaO-Zeolite catalyst is synthesized by a sonochemical impregnation-assisted drying process and calcination. The stirrer impregnation method was used as a control. CaO-Zeolite catalyst characterization and properties were identified via Scanning Electron Microscopy- Energy Dispersive X-Ray (SEM-EDX).The activation experiments were performed at an oven temperature of 120oC for 5 h and a calcination temperature of 300oC for 2 h. The synthesized catalysts of sonochemical were performed at 20 minutes, 20 kHz, and 1200 Watt, and the synthesized catalyst of stirrer were performed at 120 minutes, 1500 rpm, and 1000 watts. The experimental results revealed that the characterization of the catalysts prepared by the sonochemical method was better than that of the stirrer. Specifically, obtained CaO-Zeolite catalyst with Ca wt % increased from 0.86 wt% NZ (natural zeolite) to (11.3 wt%, 14.15 wt% and 23.48 wt%) of sonochemical and (11.82wt%, 13.95 wt% and 20.64wt%) of stirrer. The results demonstrated that Ca wt% by sonochemical in 20 minutes dispersed at support surface (zeolite) more effective than stirrer in 120 minutes. These results were impacted by acoustic cavitation and shockwave of ultrasonic on solid-liquid transport and distribution. On the other side, sonochemical assisted the activation technique to minimize particle size and allowed metal oxide (CaSO4.2H2O) to be dispersed uniformly into the pores structure of the zeolite. The utilization of sonochemical in CaO-Zeolite synthesizing enhanced catalyst activity. Keywords: CaO/Zeolite catalyst, Calcination, Drying, Sonochemical Impregnation, Ca weight percentage, Characterization